Effect of microbubble as local drug delivery system in endodontic management - An In-Vitro study - V. Shyam Ganesh; K. Vijay Venkatesh; D. Sihivahanan; Pradeep Kumar Yadalam; Deepti Shrivastava; Kumar Chandan Srivastava (Saudi Dental Journal)
Background and Objectives: Microbubbles (MBs) are gas or vapor-filled cavities inside liquids with sizes ranging from 2 to 3 µm. Recently, MBs have shown great promise in nanomedicine owing to their high encapsulation efficiency, targeted drug release, improved biocompatibility, and longer blood circulation. Furthermore, they are more suitable for focusing on particular body regions and are safer and non-invasive. MBs generators are used to create bubbles in fluid dynamics, chemistry, medicine, agriculture, and the environment. Drug delivery using MBs increases penetration without causing systemic toxicity. In this study, we examined whether the use of microbubbles as a local drug-delivery mechanism increases tubular penetration of endodontic medications and irrigant. Materials and Methods: An Enterococcus faecalis culture was added to 38 dentin cylinders of single-rooted teeth. Samples were divided into the experimental and control groups that received a triple antibiotic paste with and without MB infusion (n = 19 in each group), respectively. After 14 days, the number of live bacteria in the samples was determined using confocal laser scanning microscopy. Results: After 14 days of contact with the medication, the percentages of live and dead bacteria were assessed. Results show that Group 2 (Triple antibiotic infused micro bubble) showed significantly (P < 0.05) higher antibacterial efficacy than Group 1 (TAP). Conclusion: In this study, the antibacterial efficacy was significantly higher in the experimental group than in the control group. Therefore, within the limitations of the study it can be said that MB infusion is a viable technique to improve root canal disinfection. Hence, it can be considered as a novel technique for local drug delivery systems in endodontic management.